CRITICAL EDUCATION WITH CULTURAL IDEOLOGICAL DIMENSIONS - Anak Agung Gde Putera Semadi (Jurnal Pendidikan Kewarganegaraan Undiksha, 2021)
In an effort to develop cultured critical education, the concept of education needs to be formulated as a process of cultural dimension/humanization process. The process of education cannot be separated from human life in the context of cultural creation as well as its inheritance (cultural creation and cultural transmission) to the young generation. Through the process of critical education, humans are able to develop various potentials or creations, tastes, initiatives, and works that are at the core of the cultural process, because culture in the essential concept of education can be formulated as "The shared product of human learning". The main functions and objectives of the paradigm of developing critical education are self-awareness efforts, or also known as critical awareness, as well as developing the main methods of learning by emphasizing the principle of critical dialogic dominance. So, the core of the process of critical education is not just the transfer of knowledge/information, but it is a process of psychiatric or cultural practices towards the awareness/liberation of students. Culture studies research through a phenomenological approach can describe the answer to this problematic sharply, deeply, logically, and systematically.